Pay-as-you-go Pension Systems as Incomplete Social Contracts - Andreas Wagener (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1997)
We model a pay-as-you-go (PAYG) pension system as a series of incomplete intergenerational contracts. Each generation pays a pension to its parents as the price for a premortal transferral of economic property rights. The terms of this intergenerational trade are fixed in a social contract, which due to its long-term nature is incomplete and likely to be renegotiated after some of the initial uncertainty has been resolved. In between, however, investments and education efforts have to be carried out which affect the value of the economic resources to be transferred between generations. This set-up creates a number of intergenerational externalities (including a canonical hold-up problem) which may contribute to the explanation of those problems that real-world PAYG public pension systems currently face.
Keywords: H55; L14; D71; 330; Pay-as-you-go Pension Systems; Incomplete Contracts; Social Contracts